Differential Effects of Pharmacological Manipulations of Central α1- and a2-Adrenergic Receptors on the Secretion of Thyrotropin and Growth Hormone in Male Rats* - L. Krulich; M.A. Mayfield; Marianne K. Steele; B.A. McMillen; Samuel M. McCann; James I. Koenig (1982)
The effects of pharmacological manipulations of the two subtypes of central a-adrenergic receptors, designated α1 and α2, respectively, on the secretion of TSH and GH were tested in conscious unrestrained male rats. Intraventricular (ivt) administration of the α1-receptor agonist, methoxamine, induced a rapid and dose-related lowering of the plasma levels of both hormones, which was antagonized by systemic administration of the α1 antagonist, prazosin. Intraventricular administration of phenylephrine, another α1 agonist, also depressed plasma levels of both hormones. In contrast, the administration of relatively small doses (50 or 12.5 μg/kg, iv) of the α2 agonist, clonidine, induced large, dose-related secretory surges of both TSH and GH. The TSH/GH-stimulating effect of clonidine was inhibited in a dose-related fashion by the Α2 antagonist, yohimbine. Prazosin was ineffective against the TSH-stimulating effect, but it partially suppressed the GH secretory response, which may indicate involvement of a mixed Α1Α2 mechanism in the GHstimulating effect of clonidine. Prazosin alone, administered either iv or ivt, did not alter basal levels of the two hormones, whereas iv injection of yohimbine depressed them in a doserelated manner. Blockade of norepinephrine synthesis with a dopamine-β-hydroxylase inhibitor (DU 18288) also caused a decrease in the basal levels of both hormones and abolished the TSH, but not the GH-releasing, effect of clonidine. This suggests that a postsynaptic mechanism is involved in the activation of GH, but a presynaptic mechanism is used for activation of TSH by clonidine. These results indicate that the central noradrenergic system (s) may have two different inputs with opposite effects on the secretion of TSH and GH, respectively, depending on the type of Α-receptors involved. Activation of the Α1-receptors seems to have an inhibitory influence, whereas activation of the Α2 type appears to be stimulatory, and it seems that the Α2-receptors mediate the tonic stimulatory or facilitatory influence of the central noradrenergic system on the secretion of both hormones.